2015
DOI: 10.5534/wjmh.2015.33.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Penile Fracture: Our Experience in a Tertiary Care Hospital

Abstract: PurposePenile fracture is rare, but it is a urological emergency that always requires immediate attention. Moreover, penile fracture has been reported more frequently in recent years. It may have devastating physical, functional, and psychological consequences if not properly managed in time.Materials and MethodsThe objective of this study was to highlight the causes, clinical presentation, and outcomes of cases of penile fracture. This was a prospective observational study extending from November 2012 to Nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 28 publications
2
38
0
7
Order By: Relevance
“…The risk increases if a circumcision is not performed. In a prospective observational study, Mahapatra et al found distal necrosis in two out of three cases where a de-gloving incision was used without performing a circumcision [20]. However, Phillips et al could not show any difference in complication rates between peno-scrotal and de-gloving approach [17].…”
Section: Discussionmentioning
confidence: 99%
“…The risk increases if a circumcision is not performed. In a prospective observational study, Mahapatra et al found distal necrosis in two out of three cases where a de-gloving incision was used without performing a circumcision [20]. However, Phillips et al could not show any difference in complication rates between peno-scrotal and de-gloving approach [17].…”
Section: Discussionmentioning
confidence: 99%
“…18 Hastamızda %52,1'inin sağda, %46'sının penisin 1/3 proksimalinde olduğu görülmüştür. Cerrahi yaklaşımda insizyonun türü ve yeri operatöre bağımlıdır.…”
Section: Discussionunclassified
“…Böylece üretral ve kontralateral yaralanmalarında görülüp onarılması kolaylaşmaktadır. 18 Tunika albugineadaki defekti palpe edebildiğimiz 8 (%6,9) hastada raphe üzerinden penoskrotal insizyon, 6 (%5,2) hastada penil lateral insizyon yaparken hastaların 101 (%87,8)'inde subkoronal sirkumferensiyal insizyon tercih edilmiştir.…”
Section: Discussionunclassified
“…Ancak kontralateral ve üretral yaralanmaların tanısı ve tedavisine imkan tanıdığı için distal degloving insizyonu en yaygın kullanılan insizyondur. [18,19] Bizim olgularımızın tamamı sünnetli olduğu için ek bir kozmetik kaygıya yol açmayan sünnet insizyonu kullanı-larak degloving yapılmıştır.…”
Section: [16]unclassified
“…[19,21] Bizim serimizde üretra ve bilateral kavernoz cisim hasarı olan 12 hastada oral östrojen üretral kateter çekilene kadar (10 gün) verildi. Bu protokol hem ağrılı ereksiyonları azaltmak amacıyla hem de üretral anastomozu korumak amacıyla uygulandı.…”
Section: [16]unclassified